Evaluating the research productivity of a state university in Central Luzon, Philippines: Basis for policy recommendations - Danilo V. Rogayan Jr.; Luz N. Corpuz (Institute of Advanced Engineering and Science, 2022)
This descriptive study evaluated the research productivity of a state university in Central Luzon, Philippines, for the past five years (2016-2020) as basis for policy formulation. The study used document analysis to ascertain the research productivity in terms of: i) Number of papers published in refereed international journals such as Scopus and Commission on Higher Education (CHED) accredited journals; ii) Number of faculty researchers with publication to these journals; and iii) Total number of citations. The data were obtained primarily from online publications found in the Google Scholar and Scopus databases. Results revealed that the state university's research productivity is relatively high in terms of published papers in refereed international journals for the past five years. However, the published papers in Scopus-indexed journals and CHED accredited journals are relatively low. An average number of faculty researchers publish their works in reputable journals, but very few faculties publish in the journals recommended by the CHED. Likewise, the university had a remarkable research citation record for the past five years. The findings of this research have important implications for policy to improve research productivity and enhance the research culture in higher education institutions (HEIs). Such policies include the need to have strong support to faculty researchers, forge research collaborations, source external research funding, and establish a sound incentive mechanism.